PENGARUH AUDIT OPERASIONAL DAN SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA KARYAWAN (SURVEI PADA PT GRAHA PANGAN LESTARI) - Dennis A (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2018)
The good employee performance is generated thanks to competent of human resources and good corporate control. In the preparation of this thesis the authors do research in PT GrahaPangan Lestari. The purpose of this study is to know how much influence of operational audit and management control system to the employee performance.The method used in research is descriptive verification method, where the technique used in data collection is done by interview, questionnaire, and library research..From result of research indicate that operational audit influenced equal to 28,9% to the employee performance and management control system affecting 47.5% of the employee performance. Thus it can be concluded that operational audit within the company that has been applied properly can affect the employee performance.